Development of Virtual Field Trip (VFT) Media on Wasathiyah Islam Material at SMK Pancasila Mojowarno - Zulfah, Machnunah Ani; Maula, Hidayatul; Fodhil, Muhammad (APPLICATION: Applied science in Learning Research, 2026)
This study aims to develop and evaluate the effectiveness of Virtual Field Trip (VFT) learning media for Wasathiyah Islam material at SMK Pancasila Mojowarno, Jombang, East Java. The research employed a Research and Development (R&D) approach using the Dick and Carey model. The development stages included identifying learning objectives, conducting learning analysis, analyzing student characteristics, formulating specific goals, developing the product, designing learning strategies, preparing test items, conducting evaluations, revising the product, and performing summative evaluation. Data were collected through interviews, observations, questionnaires, and documentation. The instruments used included validation questionnaires for media and material experts employing a Likert scale, as well as pretest and posttest to measure effectiveness. Data were analyzed using both qualitative and quantitative descriptive techniques. Results revealed that the developed VFT media obtained a “Very Feasible” rating from media experts (91%) and material experts (86%). Effectiveness testing indicated a notable improvement in student achievement, with mean scores increasing from 60 on the pretest to 90 on the posttest, resulting in an N-Gain value of 0.8 categorized as high. In addition, students’ responses toward the implementation of VFT media were highly positive, with 95% in the “Very Good” category. Therefore, VFT media is effective in enhancing learning outcomes and motivation.